Organic farming in domestic law - Portugal - Couto, Rute (2023)
In Portugal there is currently a National Strategy for Organic Agriculture (ENAB) and an Action Plan (PA) for the production and promotion of organic products 2017- 2027. The ENAB has 5 strategic objectives to fulfill in a 10-year time horizon: "1) To encourage the expansion of Organic Production areas in the Agriculture, Livestock and Aquaculture sectors, by improving their technical viability and strengthening their economic attractiveness; 2) To increase the supply of agricultural and agro-food products obtained in Organic Production, promoting their competitiveness and their commercial profitability in domestic and foreign markets; 3) To develop the demand for organic products, through the structuring of the sectors, the opening of new markets, the promotion of their notoriety, their availability and the reinforcement of trust and credibility with the consumer; 4) To promote the knowledge and raise the level of competence on Organic Agriculture and Production in the specific national edafoclimatic conditions; 5) To dynamize business innovation and the availability of statistical, market and technical support information to the organic agricultural, livestock and aquaculture production.